Analisis Keperluan Penerapan Kemahiran Berfikir Aras Tinggi (KBAT) dalam Pembelajaran Teori bagi Pelajar Teknikal - Aspar, Nurul Ain Amira; Yee, Mei Heong; Mahmud, Murni Farahin; Tee, Tze Kiong; Kok, Boon Ching; Azid, Nurulwahida; Sutadji, Eddy (Research and Innovation in Technical and Vocational Education and Training, 2025)
The Technical and Vocational Education Training (TVET) system plays an important role in the economic and social development of a country. TVET aims to produce a highly skilled and competitive workforce to meet the needs of the industry. In an effort to improve the quality of TVET graduates, Higher Order Thinking Skills (HOTS) need to be applied in learning, including in theoretical subjects. However, lecturers face challenges in applying HOTS in Teaching and Learning (T&L) sessions. Therefore, this study aims to identify the needs and characteristics of the development of digital teaching modules for the application of HOTS among TVET students. This study uses a survey research design with a quantitative approach. The questionnaire was validated by three experts and distributed to 10 lecturers who teach theory courses for the Bachelor of Vocational Education (ISMPV) program at the Faculty of Technical and Vocational Education (FPTV), Universiti Tun Hussein Onn Malaysia (UTHM). The data obtained were analyzed descriptively. The results of the study showed that lecturers need flexible, easily accessible and structured digital teaching modules to assist them in applying HOTS more effectively. Therefore, the development of digital teaching modules can assist lecturers in implementing T&L more systematically and effectively. This module is also expected to improve students' thinking skills not only in academic achievement but also in their daily lives. With the appropriate module, the implementation of HOTS can be implemented more effectively, thus contributing to improving the quality of TVET graduates in Malaysia.